Pengaruh Citra Merk Dan Penerapan Harga Terhadap Keputusan Pembelian Mobil Komersial Pada PT Wicaksana Berlian Motor Cibiru Bandung - Muhammad Gibran Siregar; Halimah Zahrah (Indo Publishing, 2026)
The automotive industry plays an important role in the national economy, however, the commercial vehicle segment has shown a decline in sales in recent years. This condition is influenced by economic slowdown, rising credit interest rates, and the depreciation of the rupiah. Mitsubishi, through PT Wicaksana Berlian Motor Cibiru, has also experienced a similar trend despite maintaining a positive brand image. Based on interviews and preliminary surveys, consumers perceive Mitsubishi vehicles as durable and high-quality, yet relatively expensive compared to competitors. This indicates that purchasing decisions are influenced by a combination of brand image and pricing strategy policy. This study aims to determine the effect of brand image and price on purchasing decisions of Mitsubishi commercial vehicles at PT Wicaksana Berlian Motor Cibiru.